HUBUNGAN KELINCAHAN DENGAN KETERAMPILAN MENGGIRING BOLA BASKET PADA TIM BASKET PUTRA SMK NEGERI 2 PEKANBARU - Ardi Sofiyan Suri; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is the lack of agility athletes at the time of dribbling so that athletes look like difficulty to get through the guard and the ball is hard to be moved out of densely packed areas so the athlete is difficult to make chances to do the shooting. The cause of this is due to lack of player agility so that the effect on when players do dribble. As in the basic techniques of basketball games such as to get effective and efficient movement this needs to be based on good mastery of techniques, as for basic techniques in basketball games such as dribbling, passing, shooting, and pivot. The purpose of this research is to find out whether there is relation of agility with dribbling skills on the men's basketball team SMK Negeri 2 Pekanbaru. The population in this research is all basketball players SMK Negeri 2 Pekanbaru which amounted to 12 people. The sampling technique is the whole population (total sampling). Instrument performed in this research is dooging run test, which aims to measure the agility and skill tests herd aimed to find out how big the test results shears from the sample used. Thereafter, the data were sampled with statistics, to test the normality by the lilifors test at a significant level of a0.05. The hypothesis proposed is the relationship between agility with dribbling skills. Based on the results of the research it can be concluded as follows, from the results obtained agility has a relationship with basketball dribbling skills on the team basketball men SMK Negeri 2 Pekanbaru in karenakan, where rhitung at significant level α (0.05) = 0.602 means rhitung ( 0.6431)> rtab (0.602). Thus there is a relationship between agility with dribbling skills in the Men's Basketball Team SMK Negeri 2 Pekanbaru.Keywords: Agility, herding skills.